Pengaruh Model Pembelajaran Numbered Head Together (NHT) terhadap Hasil Belajar Fisika Siswa Kelas XI SMK ASY-SYIFA Depok Tahun Ajaran 2017/2018 - Maria Onike Manalu; Indica Yona Okyranida; Dwi Aprillia Setia Asih (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2021)
This research was conducted at SMK ASY-SYIFA Depok with a population of 97 students, with the subject of grade XI RPL 1 research as many as 32 students. The research method uses experiments with non-equivalent control group design, using experiment class XI RPL 1 using NHT learning model and control class xi rpl 2 using conventional method is not randomly selected. Intrument used in this study is a pretest question of 30 points of multiple choice questions and posttest questions a number of 30 questions that were tested first feasibility before being used for research using validity, reliability, power differences, and difficulty of the question. This study used normal and homogeneous distributed prerequisite data. Data tested using comparative averages obtained significant results with better experiment class results from control classes with a score of 82 for the experiment class and 72 for the control class.